Formation of germline chimera Gaok chicken used circulation primordial germ cells (circulation PGCs) fresh and thawed - Kostaman T; Yusuf TL; Fahrudin M; Setiadi MA; Setioko AR (Jurnal Ilmu Ternak dan Veteriner, 2014)
Formation of germline chimeras by transfer of chicken primordial germ cells (PGCs) is one of the effective techniques for preservation and regeneration of genetic resources in chickens. This study attempted to form germline chimeras of Gaok chicken buy purifying circulated PGCs of donor embryo before it is transferred to the recipient (White Leghorn chickens=WL) and studied the ability of recipient embryo on survival in incubators, and hatchability. This study used 200 fertile eggs of Gaok and 90 fertile WL breed all of the eggs was incubated at 380C and 60% humidity in a portable incubator. PGCs-circulation of the blood collected Gaok embryos at stage 14-16 were taken from the dorsal aorta, and then purified by centrifugation method using nycodenz. PGCs-circulation results further purification frozen in liquid nitrogen before being transferred to the recipient embryo. The results showed that for the development of embryos transferred to the fresh circulation of PGCs-circulation as many as 25 cells can survive up to day 14, while one of the transferred of 50 and 100 cells into recipient embryos was hatched (10%). On the contrari recipient embryos that are transferred to the frozen PGCs-circulation the embryos development was shorter, and only survived until day 10th (treatment 25 cells), day 14th (treatment of 50 cells) and day 17th (treatment of 100 cells). It is concluded that the amount of PGCs-circulation embryos transferred to the recipient is one factor that influence the success of the development germline chimeras. Key Words: Gaok Chicken, White Leghorn Chicken, Circulated PGCs, Transfer, Germline Chimera